Molecular Evidence of Orthomyxovirus Presence in Colombian Neotropical Bats - Uribe, Manuel; Rodríguez-Posada, Miguel E.; Ramirez-Nieto, Gloria C. (Frontiers in Microbiology, 2022)
The Orthomyxoviridae family includes the genera Influenzavirus, Isavirus, Quaranjavirus, and Thogotovirus. In turn, Influenzavirus can be classified into four types: α, β, γ, and δ (Formerly A, B, C, and D), from which Alphainfluenzavirus (AIV) has the broadest host range, including birds, mammals, reptiles, and amphibians. Additionally, AIV has shown global epidemiological relevance owing to its pandemic potential. The epidemiological relevance of Chiropteran due to its multiple functional characteristics makes them ideal reservoirs for many viral agents. Recently, new influenza-like subtypes have been reported in Neotropical bats, but little is known about the relevance of bats as natural reservoirs of influenza viruses. Therefore, the current study aimed to determine the presence of AIV and new influenza-like subtypes in South American bats. For a better understanding of the drivers and interactions between AIV and bats, we used molecular assays with different gene targets (i.e., M, NP, and PB1) to identify AIV in New World bats. A housekeeping gene (CytB) PCR was used to check for nucleic acid preservation and to demonstrate the bat-origin of the samples. A total of 87 free-living bats belonging to 25 different species of the families Phyllostomidae and Vespertilionidae were collected in Casanare, Colombia. As a result, this study found seven AIV-positive bat species, three of them reported for the first time as AIV prone hosts. Neither of the AIV-like analyzed samples were positive for H17N10/H18/N11 subtypes. Although additional information is needed, the presence of a completely new or divergent AIV subtype in neotropical bats cannot be discarded. Collectively, the results presented here expand the epidemiological knowledge and distribution of AIV in neotropical free-ranging bats and emphasize the need to continue studying these viruses to establish the role they could play as a threat to animal and public health.